Advancing participatory sensing and knowledge production methods for city air quality governance: Applying the Breathe London Community Programme model - Kayla Schulte; Andrew Grieve; Benjamin Barratt; Timothy Baker; Hima Coonjobeeharry; Mohammed Mead (Environmental Science & Policy, 2025)

Marine snow as vectors for microplastic transport: Multiple aggregation cycles account for the settling of buoyant microplastics to deep‐sea sediments - Nan Wu; Stuart W. D. Grieve; Andrew J. Manning; Kate L. Spencer (Limnology and Oceanography, 2025)
Many studies have reported the paradoxical observation of high concentrations of low‐density microplastics (plastic particles μ m in diameter can reach the ocean bottom. This theoretical model refines our ability to predict and understand the global and long‐term fate, transport, and inventory of microplastics in the ocean interior, the influence of microplastics on the biological carbon pump and the efficacy of plastic management policies.

Adult cardiac fibroblast proliferation is modulated by calcium/calmodulin-dependent protein kinase II in normal and hypertrophied hearts - Tamara P. Martin; Ahmed Lawan; Emma Robinson; David J. Grieve; Robin Plevin; Andrew Paul; Susan Currie (Pflügers Archiv - European Journal of Physiology, 2014)